Human Resources Performance Assessment At the Vredeburg Fort Museum Yogyakarta - Louisabethania, Angeline; Marsichoputri, Bintang Almira; Indriyani, Vivie (Ann Publisher, 2024)
Vredeburg Fortress is a symbolic manifestation of peace between the Dutch and the Palace, and it has developed into a museum that plays a role in historical tourism for the community. This study assesses human resource performance in the Vredeburg Fort Museum Yogyakarta. The method used is descriptive research with a qualitative approach and data collection techniques through observation, interviews, documentation, and direct observation at the Vredeburg Fortress. The study results show that the performance assessment at the Vredeburg fortress is influenced by critical success factors, values, independence to serve, competence that has a strategic role, administrative role, development role, performance appraisal system, occupational health and safety, and compensation. The human resources department is a group of functional positions of cultural leaders that consist of financial affairs, guest services and facilitation, correspondence, personnel affairs, and household equipment affairs. Two coordinators are the coordinator of security the cultural heritage police, and the study coordinator.